Use of Ultrasound for Sizing Tracheoesophageal Puncture Prostheses. (December 2017) - Smith, Aaron; Thimmappa, Vikrum; Jones, Julia; Shires, Courtney; Sebelik, Merry
Tracheoesophageal puncture (TEP) with voice prosthesis placement is the gold standard voice rehabilitation following total laryngectomy. Ultrasound may be useful to determine tracheoesophageal wall thickness, guiding prosthesis choice. Therefore, 14 patients undergoing total laryngectomy and TEP or prosthesis change with 16-mHz ultrasound measurement of the posterior tracheal wall were included. Seven patients underwent secondary TEP, 3 primary TEP, and 4 TEP changes. Six patients underwent flap reconstruction, while 8 patients were closed primarily. Average party wall thickness was 9.6 ± 1.7 mm, without a difference ( P = .08) between primary closure (10.3 ± 1.7 mm) and flap reconstruction (8.6 ± 1.4 mm). Change from the hypothesized sizing was noted in 11 patients (79%). Prosthesis size did not correlate with age (–0.19, P = .51), height (–0.12, P = .69), weight (0.26, P = .38), body mass index (0.22, P = .46), or flap status (–0.48, P = .079). These data suggest that ultrasound is beneficial in patients with distorted or less predictable anatomy (eg, flap reconstruction) but also important for those patients undergoing primary closure.